A new species of Physopleurus Lacordaire from French Guiana (Coleoptera, Cerambycidae, Prioninae) - Norbert Delahaye (Arquivos de Zoologia, 2015)
Misidentified as Physopleurus crassidens (Bates, 1869) since the beginning of the 20th century by some authors, a new species from French Guiana is herein described: Physopleurus ubirajarai sp. nov.